2012
DOI: 10.1152/ajprenal.00344.2011
|View full text |Cite
|
Sign up to set email alerts
|

Presence of the Ca2+-activated chloride channel anoctamin 1 in the urethra and its role in excitatory neurotransmission

Abstract: Sancho M, García-Pascual A, Triguero D. Presence of the Ca 2ϩ -activated chloride channel anoctamin 1 in the urethra and its role in excitatory neurotransmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…The CaCC anoctamin-1 (Ano1) genetically encoded by Tmem16a has been identified as the molecular correlate of the pacemaking conductance in the GI tract [31,69]. Ano1 expression has also been reported in the urethra of mice, rats and sheep; although here it was detected on smooth muscle and urothelial cells, but not on vimentin-positive ICC [80]. Cl -entry through Ano1 channels appears critical for generation of slow waves and corresponding contractile activity of the oviduct as, unlike their wild-type littermates, neonatal mice homozygous for a null allele of Tmem16a lack electrical slow wave activity in the myosalpinx [17].…”
Section: -Conductances and Uterine Pacemaker Eventsmentioning
confidence: 69%
“…The CaCC anoctamin-1 (Ano1) genetically encoded by Tmem16a has been identified as the molecular correlate of the pacemaking conductance in the GI tract [31,69]. Ano1 expression has also been reported in the urethra of mice, rats and sheep; although here it was detected on smooth muscle and urothelial cells, but not on vimentin-positive ICC [80]. Cl -entry through Ano1 channels appears critical for generation of slow waves and corresponding contractile activity of the oviduct as, unlike their wild-type littermates, neonatal mice homozygous for a null allele of Tmem16a lack electrical slow wave activity in the myosalpinx [17].…”
Section: -Conductances and Uterine Pacemaker Eventsmentioning
confidence: 69%
“…Subsequent work in various smooth muscle beds has demonstrated that ANO 1 serves a fundamental role in organizing smooth muscle contraction. In particular, ANO 1 mediated chloride current has been shown to alter cell membrane depolarization and slow waves in the GI tract [12, 13], urethra [14], and oviduct [15]. Additionally, ANO 1 is functionally expressed in airway smooth muscle and its blockade attenuates contractions as well as pro-contractile membrane associated currents [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…TMEM16A and TMEM16B channels serve a variety of functions in many cell types, including secretory epithelia (5)(6)(7)(8), gastrointestinal pacemakers (9), sensory neurons and hippocampal neurons (10)(11)(12)(13), urethral and vascular smooth muscle (14,15), and tumor cells (16). Hence, it is important to understand how these channels work.…”
mentioning
confidence: 99%